2019
DOI: 10.1111/jon.12630
|View full text |Cite
|
Sign up to set email alerts
|

Infarct Pattern, Perfusion Mismatch Thresholds, and Recurrent Cerebrovascular Events in Symptomatic Intracranial Stenosis

Abstract: BACKGROUND AND PURPOSE Studies have shown an association between infarct patterns and recurrent stroke in patients with symptomatic intracranial stenosis (sICAS) but there are limited data on associations with perfusion imaging mismatch profile. We aim to determine the association between infarct pattern, optimal mismatch profile definition, and recurrent cerebrovascular events (RCVE) in patients with anterior circulation sICAS. METHODS This is a retrospective study of consecutive patients with acutely sICAS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…This has been shown in the Vertebrobasilar Flow Evaluation and Risk of Transient Ischemic Attack and Stroke (VERITAS) study, where patients with symptomatic vertebrobasilar disease and impaired distal flow had significantly higher event rates with medical treatment than those with normal distal flow (probability at 2 years: 30% vs 13%; HR 11.55, 95% CI 1.88 to 71.00, p=0.008) 23. Furthermore, a post-hoc analysis of SAMMPRIS showed a higher risk of events in patients with anterior circulation borderzone infarcts (a pattern associated with hypoperfusion)24 25 compared with perforator or core infarcts 26. In addition, a small single-center study showed an increased risk of recurrent cerebrovascular events in patients with anterior circulation stenosis and impaired distal perfusion with tissue at risk, defined as time to maximum (Tmax) >= 6 sec versus <6 sec (50% vs 13%, p=0.05) 27.…”
Section: Discussionmentioning
confidence: 75%
“…This has been shown in the Vertebrobasilar Flow Evaluation and Risk of Transient Ischemic Attack and Stroke (VERITAS) study, where patients with symptomatic vertebrobasilar disease and impaired distal flow had significantly higher event rates with medical treatment than those with normal distal flow (probability at 2 years: 30% vs 13%; HR 11.55, 95% CI 1.88 to 71.00, p=0.008) 23. Furthermore, a post-hoc analysis of SAMMPRIS showed a higher risk of events in patients with anterior circulation borderzone infarcts (a pattern associated with hypoperfusion)24 25 compared with perforator or core infarcts 26. In addition, a small single-center study showed an increased risk of recurrent cerebrovascular events in patients with anterior circulation stenosis and impaired distal perfusion with tissue at risk, defined as time to maximum (Tmax) >= 6 sec versus <6 sec (50% vs 13%, p=0.05) 27.…”
Section: Discussionmentioning
confidence: 75%
“…The significance of IBZ as a marker for recurrent ischemic strokes has been explored in a number of previous investigations, 6,15,16 subsequently leading to perfusion imaging studies focused on IBZ 8,17 . In Yaghi et al.’s study, prespecified mismatch profile of T max > 6 s ≥ 15 ml occurred more frequently in IBZ than in other infarct patterns 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Although artery-to-artery embolism is thought to occur as a result of vulnerable plaque rupture in the main parent artery-regardless of the degree of stenosis-arterial modeling and subsequent stenosis has been associated with increasing plaque burden reaching above 50%. 14 The significance of IBZ as a marker for recurrent ischemic strokes has been explored in a number of previous investigations, 6,15,16 F I G U R E 2 Perfusion delay volume thresholds across intracranial atherosclerotic stenosis infarct pattern types. T max = time to maximum; IQR = interquartile range; BOD = branch occlusive disease; TE = thromboembolic; IBZ = internal borderzone.…”
Section: Discussionmentioning
confidence: 99%
“…Core infarct on MR perfusion was defined as apparent diffusion coefficient ≤ 620 and on CT perfusion as CBF < 30% 14,15 . Core infarct and T max‐based mismatch volumes were determined similar to prior studies, 16,17 patients were then divided into three groups: perfusion delay (total T max volume – core infarct volume) ≥ 15 cc based on T max > 6 second delay, perfusion delay volume ≥ 15 cc based on T max 4‐6 second delay, and no perfusion delay or volume ≥ 15 cc based on T max < 4 seconds. Patients meeting criteria for both T max > 6 seconds and T max 4‐6 seconds were considered as T max > 6 seconds.…”
Section: Methodsmentioning
confidence: 99%